The prevalence of the disposition effect in mutual funds' trades - Gjergji Cici (University of Cologne, Centre for Financial Research (CFR), 2011)
US equity mutual funds, on average, prefer realization of capital losses to capital gains. Nevertheless, a substantial fraction exhibits the disposition effect of realizing gains more readily than losses. My analysis suggests that learning effects have reduced the manifestation of the disposition effect over time, implying that academic research has influenced industry practices. When funds experience outflows and are managed by teams of portfolio managers they are more susceptible to selling disproportionately more winners than losers. Disposition-driven behavior affects investment style, causing lower market betas and characteristics of value-oriented and contrarian styles but has no observable effect on fund performance.
Keywords: 330